Online Media Coverage of COVID-19 in Tempo.co - Lokita, Raden Arditya Mutwara; Astari, Devi Wening; Sekarningrum, Anggun Anindya (COMMUSTY Journal of Communication Studies and Society, 2025)
When WHO (World Health Organization) declared COVID-19 a pandemic, the world realized that COVID-19 was a real threat. In Indonesia, the first case appeared on March 2, 2020. The Indonesian government categorized COVID-19 as a non-natural disaster. The aim of the research is to see how news trends appear in online media related to COVID-19, especially on Tempo.co. The research method uses content analysis with purposive sampling to process data. The data was then analyzed using the concept of news objectivity and health communication theory. As a result, 97% of COVID-19 news dimension on Tempo.co are related to health themes. The largest portion of the news is the spread of the virus, at 79%. From 840 news articles, 99% are reported in straight news. Overall, the media was successful in conveying health issues on the public agenda and was able to frame the problem (pandemic) correctly.